2018
DOI: 10.1002/tie.21993
|View full text |Cite
|
Sign up to set email alerts
|

International joint ventures research on Africa: A systematic literature review, propositions, and contextualization

Abstract: This study reviewed the research on international joint ventures (IJVs) in Africa up to 2017. The authors performed a systematic search of peer-reviewed good-quality research using the 6W procedure and ensured the quality of the review by using the 5Cs quality criteria. The content analysis was focused on four research questions. A total of 22 relevant studies were found. Overall, only about one-third of the lead authors were affiliated with African universities. A majority of the studies were quantitative, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 104 publications
(248 reference statements)
0
10
0
Order By: Relevance
“…The findings of Oguji et al (2020) showed areas that are least studied and suggested institutional theory as a promising framework. Likewise, the other studies provided their suggestions for further research.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of Oguji et al (2020) showed areas that are least studied and suggested institutional theory as a promising framework. Likewise, the other studies provided their suggestions for further research.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…We summarize the articles in the special issue within these thematic areas in the following sections. The first article—“IJVs research on Africa: A systematic literature review, propositions, and contextualization”—Oguji, Degbey, and Owusu (2020), performed a systematic literature review of IJVs research in Africa up to 2017 using the 6 W procedure and 5Cs quality criteria. A total of 22 relevant studies were found relating to IJV formation, control, ownership, governance, knowledge transfer, IJV motives, strategies and performance.…”
Section: International Joint Ventures and Acquisitions As Market Entrmentioning
confidence: 99%
See 2 more Smart Citations
“…Research shows that mergers and acquisitions (M&As), especially cross‐border ones, have become a fundamental international growth strategy for many firms from emerging or developing economies (Degbey & Ellis, 2017, 2019; Liou & Rao‐Nicholson, 2017; Oguji & Owusu, 2017; Peng, 2012). At the same time, while African countries have experienced dramatic economic growth in recent years, international business (IB) research attention on Africa has also been growing owing to the marked rise in the cross‐border economic activities of African firms (Boso, Adeleye, & White, 2016; Ibeh, Wilson, & Chizema, 2012; Oguji, Degbey, & Owusu, 2018).…”
Section: Introductionmentioning
confidence: 99%